INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - SERRANO, M S; SÁNCHEZ, M E; DE VITA, P; CARBONERO, M D; TRAPERO, A; FERNÁNDEZ-REBOLLO, P (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
Keywords: decline; Holm oak; root rot; yellow lupine

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - Serrano, M. S.; Sanchez, M. E.; De Vita, P.; CARBONERO, M. D.; Trapero, A.; FERNÁNDEZ-REBOLLO, P. (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
The following values have no corresponding Zotero field: periodical: Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas pub-location: Huesca
Keywords: decline; Holm oak; root rot; yellow lupine